The Meaning of Saraswati Holy Day Celebration in Bali - Wijnyanawati, Putu Sri; Wisnu Wardani, Dewi Ayu (International Journal of Multidisciplinary Sciences, 2024)
In Balinese Hindu society, the holy day is generally called Rerahinan. On this day, Ida Sang Hyang Widhi Wasa is believed to have descended to give his power or holy lights. This Rerahinan is commemorated based on spiritual, and moral values and the people's level of consciousness to uphold the noble values contained therein. One of the holy days that is always commemorated or celebrated in Bali is the Holy Day of Saraswati. It is celebrated as the day of the descent of science into the world. The type of research used in this research is qualitative research, data collection using observation, documentation and interviews, which are the main data sources. The data is analysed by observing, understanding, and interpreting each factor data collected and the relationship between facts. Then the research data obtained by the researcher during field research through observations and interviews with informants are described. The information obtained by the researcher is selected and coded to provide a more straightforward concept so that it is relatively easier to understand. Saraswati Holy Day celebrates Sang Hyang Widhi Wasa for his power to create knowledge and chastity. This celebration is celebrated every six months on Saturday, Umanis Wuku Watugunung. The image of the figure of Goddess Saraswati as a beautiful woman cannot be separated from Vedic theology, which describes God and his manifestation as personal virtue.